Evolutionary costs and benefits of infection with diverse strains of Spiroplasma in pea aphids. (25th April 2019) - Mathé‐Hubert, Hugo; Kaech, Heidi; Ganesanandamoorthy, Pravin; Vorburger, Christoph
Abstract: The heritable endosymbiont Spiroplasma infects many insects and has repeatedly evolved the ability to protect its hosts against different parasites. Defenses do not come for free to the host, and theory predicts that more costly symbionts need to provide stronger benefits to persist in host populations. We investigated the costs and benefits of Spiroplasma infections in pea aphids ( Acyrthosiphon pisum ), testing 12 bacterial strains from three different clades. Virtually all strains decreased aphid lifespan and reproduction, but only two had a (weak) protective effect against the parasitoid Aphidius ervi, an important natural enemy of pea aphids. Spiroplasma ‐induced fitness costs were variable, with strains from the most slowly evolving clade reaching higher titers and curtailing aphid lifespan more strongly than other strains. Some Spiroplasma strains shared their host with a second endosymbiont, Regiella insecticola . Although the result of an unfortunate handling error, these co‐infections proved instructive, because they showed that the cost of infection with Spiroplasma may be attenuated in the presence of Regiella . These results suggest that mechanisms other than protection against A. ervi maintain pea aphid infections with diverse strains of Spiroplasma, and that studying them in isolation will not provide a complete picture of their effects on host fitness.